2020
DOI: 10.3389/fnhum.2020.00251
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Enhances Retention of Visuomotor Stepping Skills in Healthy Adults

Abstract: Transcranial direct current stimulation (tDCS) paired with exercise training can enhance learning and retention of hand tasks; however, there have been few investigations of the effects of tDCS on leg skill improvements. The purpose of this study was to investigate whether tDCS paired with visuomotor step training can promote skill learning and retention. We hypothesized that pairing step training with anodal tDCS would improve skill learning and retention, evidenced by decreased step reaction times (RTs), bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Fifteen studies implemented a double-blinded design (Vines et al, 2008;Reis et al, 2009Reis et al, , 2013Williams et al, 2010;Kang and Paik, 2011;Thirugnanasambandam et al, 2011;Goodwill et al, 2013;Hendy and Kidgell, 2013;Kim and Ko, 2013;Fujimoto et al, 2014;Steiner et al, 2016;Rumpf et al, 2017;Baltar et al, 2018;Yosephi et al, 2018;Jafarzadeh et al, 2019), in which both the study personnel and participants were not aware of the types of intervention. Five studies used a single-blinded design (Stagg et al, 2011;Naros et al, 2016;Zandvliet et al, 2018;Bruce et al, 2020;Tseng et al, 2020), and the blinding was not reported in other four studies (Karok and Witney, 2013;Looi et al, 2016;Washabaugh et al, 2016;Chen et al, 2020).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Fifteen studies implemented a double-blinded design (Vines et al, 2008;Reis et al, 2009Reis et al, , 2013Williams et al, 2010;Kang and Paik, 2011;Thirugnanasambandam et al, 2011;Goodwill et al, 2013;Hendy and Kidgell, 2013;Kim and Ko, 2013;Fujimoto et al, 2014;Steiner et al, 2016;Rumpf et al, 2017;Baltar et al, 2018;Yosephi et al, 2018;Jafarzadeh et al, 2019), in which both the study personnel and participants were not aware of the types of intervention. Five studies used a single-blinded design (Stagg et al, 2011;Naros et al, 2016;Zandvliet et al, 2018;Bruce et al, 2020;Tseng et al, 2020), and the blinding was not reported in other four studies (Karok and Witney, 2013;Looi et al, 2016;Washabaugh et al, 2016;Chen et al, 2020).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…The total number of recruited participants was 784 (462 males and 322 females, age range: 18-80 years). For the design of tDCS, 19 studies used tDCS to target the M1 (Vines et al, 2008;Reis et al, 2009Reis et al, , 2013Williams et al, 2010;Kang and Paik, 2011;Stagg et al, 2011;Thirugnanasambandam et al, 2011;Goodwill et al, 2013;Hendy and Kidgell, 2013;Karok and Witney, 2013;Kim and Ko, 2013;Naros et al, 2016;Washabaugh et al, 2016;Rumpf et al, 2017;Baltar et al, 2018;Jafarzadeh et al, 2019;Bruce et al, 2020;Chen et al, 2020;Tseng et al, 2020), two studies targeted the cerebellum (Steiner et al, 2016;Zandvliet et al, 2018), one study targeted both the M1 and the cerebellum (Yosephi et al, 2018), one study targeted the primary somatosensory cortex (Fujimoto et al, 2014), and one study targeted the dorsolateral prefrontal cortex (Looi et al, 2016). The current intensities of tDCS were between 1.5 and 2 mA, and the duration of each stimulation session was between 15 to 20 min.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations